Psychometric evaluation and validation of Urdu Social Rank Scale for women with infertility in Pakistan - Mubashir, Anila Sadaf; Batool, Syeda Shahida; Arafat, S. M. Yasir (Frontiers in Psychiatry, 2023)
Background: Infertility negatively affects nearly all aspects of women's life and is a source of demotion in the rank/ status of women that they have achieved after marriage. This social rank/status demotion due to infertility may result in depression and several other psychopathologies. No extant instrument is available to measure the phenomenon of social rank in women with infertility in Pakistan. Objective: The aim of the current study was to evaluate the psychometric properties and validate the Social Rank Scale for women experiencing infertility in Pakistan. Methodology: This study was conducted in four phases. The data were collected from females with primary infertility who visited hospitals all over Pakistan from 2016 to 2018. Social Rank Scale comprising (SRS) of two scales; Social Comparison Scale (SCS) and the Submissive Behavior Scale (SBS) was developed. The factor structure for both scales was confirmed via confirmatory factor analysis among a sample of 210 participants with good model fit indices. Results: The factor structure of 37 items of SCS-WI and of 21 items of SBS-WI was determined through exploratory factor analysis (EFA) on a sample of 215 women with primary infertility with an age range of 20-45 years (Mage= 31.03; SD= 6.18). Principal component analysis with varimax rotation method yielded three factors solution for SCS-WI and 32 items were retained for SCS-WI that accounted for 62.38% variance. For SBS-WI uni-factor solution was obtained and 20 items were retained for SBS-WI which collectively accounted for 42.01% variance. Conclusion: The study provides acceptable psychometric properties of the SRS Scale for women with infertility in Pakistan among women with primary infertility. Testing of psychometric properties in different groups of samples would justify the generalized use of the instrument.